2012
DOI: 10.1016/j.cardfail.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cardiomyopathy: Importance of Genetic and Metabolic Evaluation

Abstract: Background-Cardiomyopathy is a heterogeneous disease with a strong genetic component. A research-based pediatric cardiomyopathy registry (PCMR) identified familial, syndromic, or metabolic causes in 30% of children. However, these results pre-dated clinical genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 31 publications
(51 reference statements)
5
68
0
7
Order By: Relevance
“…22,23 This patient also harbors a heterozygous missense mutation, c.1979G>A (p.R660H), which was found to be in trans with the exon 18 deletion by parental testing. 24,25 Because this patient is a compound heterozygote with a missense mutation and an exonic deletion, this result confirms the diagnosis of Pompe disease.…”
Section: Comprehensive Analysis Of Exonic Deletions Is Feasible Basedsupporting
confidence: 70%
“…22,23 This patient also harbors a heterozygous missense mutation, c.1979G>A (p.R660H), which was found to be in trans with the exon 18 deletion by parental testing. 24,25 Because this patient is a compound heterozygote with a missense mutation and an exonic deletion, this result confirms the diagnosis of Pompe disease.…”
Section: Comprehensive Analysis Of Exonic Deletions Is Feasible Basedsupporting
confidence: 70%
“…Previously, it was reported that approximately 5% of pediatric cardiomyopathies are due to an inborn error of metabolism [2] , however a more recent study found a substantially higher percentage, with 26% of hypertrophic and 16% of dilated cardiomyopathies having a metabolic etiology [3] . A separate study found five out of 35 infants (13.5%) diagnosed in the first year of life had a metabolic etiology to their cardiomyopathy [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Вместе с тем у детей гораздо чаще по сравнению со взрослыми причиной кардиомиопатий являются генетически детерминированные метаболические де-фекты. Так, если в более ранних исследованиях было показано, что врожденные нарушения обмена веществ служат причиной кардиомиопатий в 5% случаев [3], то в настоящее время установлено, что нарушения ме-таболизма значительно чаще вызывают развитие это-го заболевания -в 26 и 16% случаев соответственно гипертрофическая и дилатационная кардиомиопатии имеют метаболическую природу [10].…”
unclassified
“…Первый принцип базируется на характеристике нарушений обмена веществ: нарушения метаболизма аминокислот, ор-ганических кислот, жирных кислот, дефекты транс-порта карнитина, обмена гликопротеинов, глико-гена, дефекты гликозилирования. Второй принцип классификации основан на изменении органелл клетки: выделяют лизосомальные болезни накопле-ния, митохондриальные и пероксисомные заболева-ния [8][9][10][11]. Наиболее часто встречаются нарушения окисления жирных кислот, органические ацидурии, болезни накопления, в то время как врожденные де-фекты гликозилирования и митохондриальные бо-лезни реже диагностируются у детей первых лет жиз-ни с кардиомиопатиями [8,10,12,13].…”
unclassified
See 1 more Smart Citation